Treatment Zone Decentration During Orthokeratology on Eyes with Corneal Toricity. Issue 9 (September 2016) - Maseedupally, Vinod K.; Gifford, Paul; Lum, Edward; Naidu, Rajeev; Sidawi, Dyana; Wang, Bingjie; Swarbrick, Helen A.
ABSTRACT: Purpose: To compare the magnitude of treatment zone decentration between eyes with minimally toric corneas (⩽1.50 DC, LoTor group) and eyes with moderately toric corneas (1.50 to 3.50 DC, HiTor group) after a single overnight wear of spherical orthokeratology lenses. Methods: In the LoTor group, 21 participants (9 M, 12 F, 20–40 years) were fitted using a conventional fitting approach based on the flat corneal meridian. In the HiTor group, 12 participants (5 M, 7 F, 19–45 years) were fitted using the conventional fitting method in one eye (HiTor group I) and the other eye was fitted with a lens with slightly deeper sagittal height (HiTor group II). In all groups, BE spherical orthokeratology trial contact lenses (Boston XO) were used and corneal topography data (Medmont E300) were obtained at baseline and after a single overnight wear. The magnitude of treatment zone decentration relative to vertex normal was determined from corneal topography refractive power difference maps. Treatment zone parameters including magnitude and direction of decentration were analyzed and related to baseline corneal parameters. Results: After a single overnight wear, the mean magnitude of treatment zone decentration was 0.48 ± 0.20 mm in the LoTor group, 1.06 ± 0.57 mm in HiTor group I, and 0.95 ± 0.44 mm in HiTor group II. Treatment zone decentration in the LoTor group was significantly different from HiTor group I ( p < 0.001), both fitted using a conventional fitting method. Treatment zone decentration was not significantly different between HiTor group I and II (p = 0.606). The magnitude of treatment zone decentration was positively correlated with the amount of baseline corneal toricity (LoTor and HiTor group I combined, p = 0.048). Conclusions: Eyes with higher amounts of corneal toricity give rise to increased amounts of treatment zone decentration in overnight orthokeratology.